Evidence for Hand-Size Constancy: The Dominant Hand as a Natural Perceptual Metric. (November 2014) - Linkenauger, Sally A.; Geuss, Michael N.; Stefanucci, Jeanine K.; Leyrer, Markus; Richardson, Beth H.; Proffitt, Dennis R.; Bülthoff, Heinrich H.; Mohler, Betty J.
The hand is a reliable and ecologically useful perceptual ruler that can be used to scale the sizes of close, manipulatable objects in the world in a manner similar to the way in which eye height is used to scale the heights of objects on the ground plane. Certain objects are perceived proportionally to the size of the hand, and as a result, changes in the relationship between the sizes of objects in the world and the size of the hand are attributed to changes in object size rather than hand size. To illustrate this notion, we provide evidence from several experiments showing that people perceive their dominant hand as less magnified than other body parts or objects when these items are subjected to the same degree of magnification. These findings suggest that the hand is perceived as having a more constant size and, consequently, can serve as a reliable metric with which to measure objects of commensurate size.